Stacking of doxorubicin on folic acid-targeted multiwalled carbon nanotubes for in vivo chemotherapy of tumors - Yan Yan; Ruizhi Wang; Yong Hu; Rongyue Sun; Tian Song; Xiangyang Shi; Shimeng Yin (Taylor & Francis Group, 2018)
In this work, we developed a novel active targeting and pH-responsive system for delivering the drug doxorubicin (DOX) to tumor sites using folic acid (FA)-modified multiwalled carbon nanotubes (MWCNTs). Acid-treated MWCNTs with carboxyl groups were first covalently conjugated with polyethyleneimine (PEI). Subsequent sequential modification with FA (via a polyethylene glycol spacer), fluorescein isothiocyanate (FI), and acetic anhydride/triethylamine resulted in multifunctional FA-bound MWCNT (MWCNT-PEI.Ac-FI-PEG-FA) nanomaterials that possessed exceptional colloidal stability and good biocompatibility in a given concentration range. The FA-bound MWCNTs were characterized using various techniques and exhibited a high drug loading and an encapsulation efficiency as high as 70.4%. DOX/MWCNT-PEI.Ac-FI-PEG-FA nanocomplexes (DOX/MWCNT NCs) exhibited pH-responsive release in acidic environments. Importantly, the DOX/MWCNT NCs targeted tumor cells overexpressing FA receptors (FARs) and effectively inhibited their growth. In vivo anticancer experiments demonstrated that DOX/MWCNT NCs not only enhanced the suppression of tumor growth but also decreased the side effects of free DOX. The developed FA-modified MWCNTs with an unconventionally high DOX loading boosted in vivo anti-tumor efficacy, and the lower systemic toxicity may be utilized for tumor therapy upon clinical translation.